Responses of candidate intensity measures to different mental and motor load levels using upper limb exergames in typically developing children and adolescents - Gaizka Goikoetxea-Sotelo; Livia Rätzo; Hubertus J. A. van Hedel (PLoS ONE, 2025)
Background In (pediatric) neurorehabilitation, high-intensity therapy is well-recognized for enhancing rehabilitative outcomes. However, measures that consider the different aspects of therapy intensity are lacking. Therefore, a better understanding of how to measure therapy intensity during upper-limb neurorehabilitation is needed. Objectives To investigate the response of heart rate variability (HRV), skin conductance (SC), activity counts and movement repetitions normalized for the maximal capacity (%ACmax and %MOVmax, respectively), and the NASA-TLX scale to different mental and motor intensity levels of two self-developed upper limb exergames in typically developing children. We also investigate the effects of age on the responses of the measures. Methods In this cross-sectional study, participants engaged in one mental and one motor exergame. For each exergame, they played three personalized intensity levels (“very easy,” “challenging,” and “very difficult”), each lasting three minutes. We analyzed the responses of all measures for each intensity level and exergame. Results 21 children and adolescents (9 females) aged 5.2 to 17.9 years participated in the study. HRV, %ACmax, and %MOVmax responded to increased motor intensity. SC did not respond to increases in mental or motor intensity levels. The NASA-TLX responded to increases in motor intensity levels but only partially to increases in mental intensity. Finally, age showed significant effects only on %MOVmax. Conclusion Changes in mental intensity were more challenging to capture than changes in motor intensity. As each measure responded to different aspects of therapy intensity, a combination of measures, e.g., HRV, %ACmax, and NASA-TLX effort, might be the best strategy for assessing therapy intensity multidimensionally. Although the measures hold considerable potential, future studies should determine the responses of the measures and their psychometric properties in the target group.